Black To Pink Gel: The Antibacterial Potency Of Curcuma Domestica And Moringa Oleifera Extract Gel Against P.Gingivalis (A Pilot Study) - Sukmawati, Ayuda Nur; Megawati, Ani; Pratiwi, Devy Anugraeni (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2025)
Periodontitis continues to be a debilitating problem when improperly treated. This condition is associated with certain periodontopathological bacteria, including Porphyromonas gingivalis. Chlorhexidine, while proven effective against bacteria in the oral cavity, carries unwanted side effects. Curcuma domestica and Moringa oleifera are domestic herbs that possess several therapeutic effects. This study aims to investigate the antibacterial effect of the combined two herbs in extract gel. This experimental study used three combination formulas of C. domestica: M. oleifera (0.1%:2%, 0.5%:4%, 0.9%:6%) as the test group and chlorhexidine as the positive control group. The antibacterial inhibition disc method was used to determine the antibacterial activity in each group. The statistical analysis was carried out with Kruskal-Wallis and continued with the Mann-Whitney test. In this study, extract gel combination of Curcuma domestica and Moringa oleifera at concentrations of (0.1%:2%; 0.5%:4%; 0.9%:6%) can inhibit the growth of Porphyromonas gingivalis with average inhibition zone diameters of 12.50 mm, 14.49 mm and 16.66 mm, respectively. The inhibition zone falls in the strong category. The control group showed a mean inhibition zone of 20.96, which is classified as a very strong inhibition zone. Although there was a significant p-value between the test and control groups, the results suggested the potential of the extract gel as an alternative for treating periodontitis with lesser side effects.